PENGARUH PENYIMPANAN URINE TERHADAP JUMLAH lEUKOSIT DAN ERITROSIT PADA PENDERITA INFEKSI SALURAN KEMIH DENGAN METODE SY (STANDARD YIELD) - Edy Haryanto; Pestariati .; Anik Handayati; Sri Sulami Endah Astuti (JURNAL PENELITIAN KESEHATAN, 2015)
Urinary tract infection ( un ) is a pathological condition that is often encountered and marked with urinesediment results indicate nitrite, leucocytes and positive bacteria. In some hospitals, inpatient specimendelivery is often delayed, causing delayed examination. Urine samples should be examined, therefore itis kept at room temperature, lysis of erythrocytes and leukocytes and urine will turn into alkaline. Thisstudy aims to prove how much the influence of the long treatment of urinary tract infection to the numberof leukocytes and erythrocytes urine sediment . "This type of research is quantitative analysis " todetermine the number of leukocytes and erythrocytes urine sediment urinary tract infection sufferers whoimmediately performed ( 0 hours) , stored for 2 hours, 3 hours and 4 hours using SY ( standard yield) .The results of the examination number of leukocytes to the 20 sediment samples with immediate unpatients obtained an average of 59 cells / mL , after the delay of 2 hours earned the average of 35 cells /mL, 3 hours on the average of 18 cells / mL and 4 hours obtained an average of 12 cells / uL. The resultsof the examination of erythrocyte sediment amount to ISK 20 patient samples obtained immediatelyperformed the average of 20 cells / mL , after the delay of 2 hours earned the average of 14 cells / mL , 3hours on the average of 9 cells / mL and 4 hours obtained the average of 6 cells / mL . From the Post Hoctest results obtained three treatment groups proved no longer influence to urinary tract infections.suspension 0 hour, 2 hours, and 3 hours to the number of leukocytes and erythrocytes urine sediment.There is no longer influence to urinary tract infections suspension 3 hours and 4 hours on the number ofleukocytes and erythrocytes urine sediment.Key words: ISK, Sedimen urtn, /eukocit dan erithrocit.